DESCRIPTIVE STUDY OF WAITING TIME FOR PRESCRIPTION SERVICES AT THE PHARMACY INSTALLATION OF ROEMANI MUHAMMADIYAH HOSPITAL SEMARANG - Ratna Wulandari; Sri Suwarni; Qorri Ainun Naimah (Universitas Pahlawan Tuanku Tambusai, 2023)
Hospitals are health facilities that provide health services evenly by prioritizing efforts to cure disease and restore health, which are carried out in harmony and integrated with efforts to improve health and prevent disease in a referral setting, and can be utilized for education and research personnel. Waiting time for prescription services is a major factor in patient satisfaction in services provided at the hospital. If a patient who seeks treatment at the hospital waits for a prescription for a longer time, then his satisfaction will be lower than the shorter waiting time. The purpose of this study was to determine the waiting time for prescription services at the Roemani Muhammadiyah Hospital Pharmacy Installation in Semarang. This research method is a descriptive study with a total population of 1000 subjects and a sample of 240 subjects. The sampling technique used was random sampling. The research was carried out from May to August 2019. Data analysis used descriptive statistic analysis. The average waiting time for prescription services is 62 minutes for concoction recipes and 33 minutes for non-concoction recipes. The conclusion in this study is that the waiting time for prescription services at the Roemani Muhammadiyah Hospital Pharmacy Installation in Semarang is not in accordance with the recommendations of the Ministry of Health, namely ? 30 minutes for non-concoction drugs and ? 60 minutes for concoction drugs